How to Envision a Future after Disaster: Cinematic Landscape and Post-Disaster Recovery in Haruka Komori and Natsumi Seo’s Double Layered Town/Making a Song to Replace Our Positions (2019) - Motegi, Aya (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2025)
Since the 2011 Great East Japan Earthquake, many films have depicted the destruction and its immediate aftermath. Existing literature largely focuses on these works, overlooking how filmmakers have dealt with the concerns that arose years later when the post-disaster reconstruction project was deemed largely completed. This paper examines how Haruka Komori & Natsumi Seo’s documentary Double Layered Town/Making a Song to Replace Our Positions (2019) addresses long-term issues accompanying the post-disaster recovery, including landscape transformation and the intergenerational transmission of survivors’ memories. Through a close analysis of the film’s aesthetics, this paper argues that its landscape shots and ethical perspectives challenge the progressive narrative of reconstruction often promoted by authorities while also visually questioning the meaning of post-disaster recovery.